2000
DOI: 10.1212/wnl.54.2.415
|View full text |Cite
|
Sign up to set email alerts
|

Early-life risk factors and the development of Alzheimer’s disease

Abstract: The early-life childhood and adolescent environment is associated with the risk of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 27 publications
8
106
0
Order By: Relevance
“…Evidence suggests an association between Alzheimer's disease and education (Mayeux and Stern 2012;Meng and D'Arcy 2012;Stern 2012); exercise (Farina et al 2014); social activity (Reed et al 2011); and physical health, including stroke (Willis and Hakim 2013), hypertension (Borenstein et al 2006), body mass index (BMI), and diabetes (Profenno et al 2010). There is mixed evidence for whether mid-to later-life cognitive function is associated with socioeconomic status (SES) (Cagney and Lauderdale 2002;Kaplan et al 2001;Luo and Waite 2005;Moceri et al 2000;Singh-Manoux et al 2005Turrell et al 2002;Zeki Al-Hazzouri et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests an association between Alzheimer's disease and education (Mayeux and Stern 2012;Meng and D'Arcy 2012;Stern 2012); exercise (Farina et al 2014); social activity (Reed et al 2011); and physical health, including stroke (Willis and Hakim 2013), hypertension (Borenstein et al 2006), body mass index (BMI), and diabetes (Profenno et al 2010). There is mixed evidence for whether mid-to later-life cognitive function is associated with socioeconomic status (SES) (Cagney and Lauderdale 2002;Kaplan et al 2001;Luo and Waite 2005;Moceri et al 2000;Singh-Manoux et al 2005Turrell et al 2002;Zeki Al-Hazzouri et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that early-life environments (such as childhood socioeconomic situation) may affect the development of obesity and dementia. 13,14 The life course development of the adipositydementia association has been suggested, 15 but the contribution of genetics and early life environments to the relationship has not been investigated. In the present study, we sought to 1) verify the long-term effect of midlife overweight and obesity measured by BMI on the risk of dementia, Alzheimer disease (AD), and vascular dementia (VaD) taking into account diabetes and lifespan vascular disorders using unmatched case-control analysis; and 2) explore whether genetic and early-life environments could explain the observed association between midlife adiposity and dementia by cotwin matched case-control approach using data from the Swedish Twin Registry.…”
mentioning
confidence: 99%
“…In addition, Ott et al, (22) reported that the high age of the father at the time of birth and the lack of major gene are the risk factors for developing Alzheimer; the finding indicated a weak relationship between the age of mother and Alzheimer disease. Unlike the findings of the current study, Moceri et al, (47) evaluated the conditions of the first 18 years of life in patients with Alzheimer. According to this study, the risk of Alzheimer rises as 1 child is added to the family.…”
mentioning
confidence: 66%